Canadian Anatomic Kidney Score: Quantitative Macroscopic Assessment of Donor Kidney Quality for Transplantation - Danny Matti, BMSc, MD; Juliano Offerni, MD; Pavel S. Roshanov, MD; Jirong Lu, MBBS; Yanbo Guo, MD; Victoria Lebedeva, MSc; Erica Ai Li, BSc; Haider Abed, BSc, MD; William Luke, BSc, MD; Alp Sener, MD; Patrick P. Luke, MD (Transplantation Direct, 2024)
Background. The Canadian Anatomic Kidney Score (CAKS) is a novel 6-point grading system that standardizes the gross description of a donor kidney across 3 components—vessels, anatomy, and sticky fat. We hypothesized that the CAKS predicts allograft functional outcomes and provides additional information to the Kidney Donor Profile Index (KDPI) and histologic assessment of the donor kidney. Methods. Single-center cohort of 145 patients who underwent renal transplantation with CAKS analysis between 2018 and 2021. CAKS was prospectively determined before transplantation. Preimplantation core biopsies were assessed according to the Remuzzi score (RS). The primary outcome was 1-y allograft function represented by an estimated glomerular filtration rate (eGFR). Results. Linear regression without adjustment for KDPI or RS showed a significant association between the CAKS and 1-y eGFR (−8.7 mL/min/1.73 m2 per point increase in CAKS; 95% CI, −13.0 to −4.4; P < 0.001). Most of that association was attributed to the vessel component (−12.1; −19.4 to −4.8; P = 0.002). Adjustment for KDPI and RS attenuated the relationship between 1-y function and CAKS (−4.6; −9.5 to 0.3; P = 0.065) and vessel component (−7.4; −15.2 to 0.5; P = 0.068). Conclusions. Anatomic assessment of donor kidneys at the time of transplantation associates with allograft function at 1 y. Vascular assessment appears to make the dominant contribution.